Penentuan Sektor Basis dan Strategi Pengembangan Sektor Non Basis di Kabupaten Banjar Tahun 2010-2018 - Muhammad Rizky Rifani; Chairul Sa’roni (PPJP Universitas Lambung Mangkurat, 2020)
AbstractThe purpose of this study is to (1) determine the base sector owned by the Banjar Regency, and (2) the non-base sector development strategy in Banjar District. The analysis method to determine the base sector is calculated through Location quotient, Shift Share, and Klassen Typology for development strategies through SWOT analysis. Using secondary data in the form of gross regional domestic product according to employment at constant prices and primary data obtained from interviews with respondents who are considered experts or know the situation. The results showed four primary sectors: construction sector, wholesale and retail trade sector, car and motorcycle repair sector, accommodation and food and beverage supply sector, and the Information and Communication sector. The industry that wants to be developed is the agriculture, forestry, and fisheries sectors that produce the strategy that best suits the situation is the S-O strategy.